2016
DOI: 10.1039/c6pp00082g
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with intralesional methylene blue and a 635 nm light-emitting diode lamp in hidradenitis suppurativa: a retrospective follow-up study in 7 patients and a review of the literature

Abstract: Hidradenitis suppurativa is a chronic inflammatory skin disease which has an estimated prevalence of 1%. It is characterized by the formation of recurrent painful suppurative nodules and abscesses in the flexural areas of the body. It is believed that its pathogenesis involves an aberrant, genetically-determined activation of innate immunity against the bacterial commensal flora of intertriginous areas. It has been found that the formation of antibiotic-resistant bacterial biofilms is a common finding in hidra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 62 publications
0
18
0
11
Order By: Relevance
“…Uncertain results have been obtained with intralesional PDT [74][75] . Agut-Busquet et al [76] recently reported a retrospective experience in the treatment of HS with PDT using intralesional methylene blue and a 635-nm light-emitting diode lamp in 7 patients. At 1 month follow-up, good response was achieved in 6 patients.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…Uncertain results have been obtained with intralesional PDT [74][75] . Agut-Busquet et al [76] recently reported a retrospective experience in the treatment of HS with PDT using intralesional methylene blue and a 635-nm light-emitting diode lamp in 7 patients. At 1 month follow-up, good response was achieved in 6 patients.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%
“…After six months, five patients (71%) maintained remission of the disease in the treated area. Photodynamic therapy has been used for its ability to reduce bacterial biofilms, which is a common finding in hidradenitis lesions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other frequent therapies were topical antibiotics (48%), intralesional steroids (40%) and photodynamic therapy (PDT) with intralesional methylene blue and 635 nm light-emitting diode lamp (28%) as previously described. 12 Surgical treatment was carried out in 20% of the patients with VHS and biologic therapy (adalimumab, infliximab and ustekinumab) was prescribed in 16% of them. All cases improved in quality of life and pain control.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%